Spatial and Temporal Fluctuations of Pore‐Gas Composition in Sulfidic Mine Waste Rock. Issue 10 (29th September 2016) - Lorca, Maria E.; Mayer, K. Ulrich; Pedretti, Daniele; Smith, Leslie; Beckie, Roger D.
Abstract : Core Ideas: Grain‐size segregation during end dumping affects the pore‐gas distribution. Seasonal variations in precipitation affect O2 ingress and CO2 egress. Hot spots of sulfide oxidation are controlled by physical and chemical heterogeneity. Grain‐size segregation is reflected in the spatial distribution of oxidation rates. The oxidation of sulfide minerals and pH‐neutralization reactions in unsaturated mine waste rock produce changes in the pore‐gas composition, leading to substantial deviations from atmospheric conditions. We studied the temporal and spatial changes in pore‐gas composition, temperature, and volumetric water content (VWC) in an experimental pile during a 2‐yr period. The pile was constructed by end dumping and is exposed to a marked two‐season (wet–dry) climate. The grain‐size segregation of waste rock occurring during end‐dump construction significantly affected the spatial distribution of pore‐gas composition within the pile. Results from continuous monitoring also demonstrated the role of VWC fluctuations on pore‐gas composition at the study site. Oxygen decreased during the wet season, while CO2 concentrations showed the opposite behavior. Gaseous diffusion was inferred as an important O2 supply mechanism for this experimental waste‐rock pile. In addition, wind‐induced gas advection and convection probably contributed to O2 ingress into the basal regions of the pile. Intrinsic oxidation rates were estimated based on one‐dimensional reaction–diffusion modeling, showing pronounced variations between the top and bottom of the pile. These differences can be attributed to low reactivity in the basal region of the pile related to the coarse‐grained nature of the material and the omission of O2 –supply mechanisms other than diffusion. The results demonstrate the complex interactions between physical and chemical heterogeneities in mine waste rock and contribute to an improved understanding of oxidation reactions and metal release that occur in sulfidic waste rock.